Unexpected Ritter Reaction During Acid‐Promoted 1, 3‐Dithiol‐2‐one Formation. Issue 5 (17th May 2013) - Dumur, Frédéric; Mayer, Cédric R.
Abstract A series of aryl‐substituted 1, 3‐dithiol‐2‐ones was prepared by the BhattacharyaHortmann cyclization method. Unexpectedly, a Ritter reaction occurred during the acid‐catalyzed cyclization at the cyano group of the aryl substituents and 1, 3‐dithiol‐2‐ones bearing a carboxy or a carboxamide group could be selectively obtained (see 1 and 2a in Scheme 1). The formation of the acid or the amide functionality was temperature‐dependent so that the one or the other group could be introduced selectively by modifying the reaction temperature.